High-yield and high-calorific bio-oil production from concentrated sulfuric acid hydrolysis lignin in supercritical ethanol - Riaz, Asim; Kim, Chang Soo; Kim, Yunje; Kim, Jaehoon (Elsevier BV, 2016)
The aim of this work is to explore process parameters (pressure, time, formic acid content) for producing high-yield and high-calorific bio-oil from concentrated sulfuric acid hydrolysis lignin (CSAHL) with formic acid as an in-situ hydrogen source in supercritical ethanol (scEtOH). Even at short reaction time of 30 min, high conversion of 92% and high bio-oil yield of 85 wt% were observed at 350 degrees C and formic-acid-to-lignin mass ratio of 1.5 using a stirred reactor. The effective deoxy-liquefaction nature associated with scEtOH with aid of formic acid resulted in significant reduction in oxygen content of 44% and high higher heating value of 31.2 MJ kg(-1) of produced bio-oil. The overall process is energetically efficient with 112% energy recovery (ER) and 78% energy efficiency (EE). The results are compared with Kraft lignin (KL) under identical reaction conditions. The inherent recalcitrant nature of CSAHL resulted in lower conversion and lower bio-oil yield when compared to the liquefaction of Kraft lignin (KL, 99% conversion, 90 wt% bio-oil yield). Bio-oil with better flow properties, low molecular weight, and a high amount of monomeric phenol was produced after 60 min of reaction. The compounds in the bio-oil were mainly phenols, esters, furans, alcohols, and traces of aliphatic hydrocarbons. (C) 2015 Elsevier Ltd. All rights reserved.